2016
DOI: 10.1002/aic.15196
|View full text |Cite
|
Sign up to set email alerts
|

Minimum fluidization velocity in gas‐liquid‐solid minifluidized beds

Abstract: The initial fluidization characteristics of gas-liquid-solid minifluidized beds (MFBs) were experimentally investigated based on the analyses of bed pressure drop and visual observations. The results show that U Lmf in 3-5 mm MFBs can not be determined due to the extensive pressure drop fluctuations resulting from complex bubble behavior. For 8-10 mm MFBs, U Lmf can be confirmed from both datum analyses of pressure drop and Hurst exponent at low superficial gas velocity. But at high superficial gas velocity, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Visual observation and hydrostatic pressure drop analysis of the multiphase flow are frequently used to estimate U Lmf . Additionally, U Lmf L.s is calculated by mathematical, fractal, disorder, wavelet, and neural network analyses [32]. The Ergun equation (Ergun [46]) is the generally known model for determining a fluid's minimum fluidization velocity to fluidize the particle [47].…”
Section: Minimum Fluidization Velocity (U Lmf )mentioning
confidence: 99%
See 2 more Smart Citations
“…Visual observation and hydrostatic pressure drop analysis of the multiphase flow are frequently used to estimate U Lmf . Additionally, U Lmf L.s is calculated by mathematical, fractal, disorder, wavelet, and neural network analyses [32]. The Ergun equation (Ergun [46]) is the generally known model for determining a fluid's minimum fluidization velocity to fluidize the particle [47].…”
Section: Minimum Fluidization Velocity (U Lmf )mentioning
confidence: 99%
“…Many articles have been reported on the minimum velocity of fluidized beds in three phases (Begovich and Watson, [3]; Fortin, [48]; Costa et al, [49]; Song et al, [50]; Nacef et al, [51]; Zhang et al, [52]; Ramesh et al, [53]; Ruiz et al, [54]; Sivasubramanian et al [34]; Jena et al, [2] and Li et al, [32]). Many studies of the minimum fluidization velocity in three-phase fluidized beds are limited to air-water glass bead systems whose particle density exceeds that of the liquid by a factor of 2 to 3 [25].…”
Section: Minimum Fluidization Velocity (U Lmf )mentioning
confidence: 99%
See 1 more Smart Citation
“…Microreactors produced by micromachining technology outperform conventional macroscale counterpart installations in terms of heat and mass transfer, and thus they can achieve a higher efficiency of production. In addition, the low cost, safe as well as controllable operation, and easy accident handling are also the unique advantages of these microscale devices. , In view of this, microfluidized beds with the inner diameter or cross-section side length in the millimeter , or even submillimeter order emerge as a novel type of process-intensified reactor that combines the advantages of microtechnology systems and fluidized beds. They hold significant potential for application in the field of process industries and have been gaining increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Among the researches on the mini-scale multiphase flow systems, there have been some reports on the micro-or mini-scale fluidized beds. The main topics are to determine the hydrodynamic parameters of the mini-fluidized bed, such as flow regime, minimum fluidization velocity, minimum bubble velocity, bubble size, bubble terminal velocity, and so on, [16][17][18][19][20][21][22][23][24][25] by means of pressure drop measurement and high-speed photography. Compared with conventional fluidized beds, it is found that some factors negligible in macro flow play a major role in mini-flow systems, such as flow regime transitions influenced by the ratio of bed to particle diameter, which can be attributed to local heterogeneous fluidization caused by wall effect.…”
mentioning
confidence: 99%